Svekofennialaisen orogenian ylityönnön terminen mallinnus Itä-Suomen arkeeisella kratonilla - Kaislaniemi, Lars (Helsingfors universitet, 2011)
This study reviews the thermophysical properties of rocks and the lithosphere and describes a one dimensional thermal numeric model of hypothetical 20 km thick overthrust plate obtruded on to the Archeaen craton in the Svecofennian orogeny (1.92-1.77 Ga). The objective is to find out if the overthrust plate and its radiogenic heat sources were able to produce the thermal effects observed on the current erosion level of the Archaean craton. Heat transfer in lithosphere is assumed conductive, and advective heat transfer due to melting and melt transfer is supposed negligible. The study area is located in the Eastern Finland, approximately current Kainuu and Northern Karelia regions, east from the most active orogenic belt (Raahe-Ladoga zone), so that orogenic magmatism can be neglected. Physical parameters and boundary conditions for the model are from different earlier published sources: deep seismic profiles (rock variation in depth), laboratory measurements (heat production and conductivity of rocks), field measurements (heat flow densities), and pT(t) estimations from the Finnish precambrian to estimate the size and thickness of the sheet. Comparison of the modelling results to previous K-Ar datings and other pTt estimations show, that the effect of the overthrust sheet has been adequate (max. T 450°C at 4 kbar) to produce the K-Ar resetting ages measured from the Archaean bedrock at current erosion level. No other kind of thermal activation in lithosphere is required. Results show possibly very minor partial melting in upper middle crust underneath the overthrust sheet. Tässä työssä luodaan katsaus kivien ja litosfäärin lämpöfysiikkaan sekä kootaan yksiulotteinen numeerinen terminen malli hypoteettisesta 20 km paksusta ylityöntölaatasta, joka on svekofennialaisessa orogeniassa (1,92 1,77 Ga) työntynyt arkeeisen kratonin päälle. Tavoitteena on selvittää, riittääkö ylityöntölaatan kuorta paksuntava ja mukanaan tuomien radiogeenisten lämmönlähteiden vaikutus aiheuttamaan arkeeisella kratonilla havaitut ...